Understanding Types and Development Processes of Family - Radhika Kapur, (Indian Journal of Social Science and Literature (IJSSL), 2024)
The main objective of this research paper is to acquire an understanding of the types and development processes of family. In India, there are urban and rural communities throughout the country. In both communities, the families are of two types, i.e. nuclear and joint. The family members are required to put into operation different types of job duties, which are facilitating in leading to effective growth and development of the families. Furthermore, they are required to augment their information in terms of different types of methodologies and procedures. These are complicated and manageable. The individuals are required to work in collaboration and integration with each other in putting into operation methodologies and procedures in an efficient manner. One of the important aspects that needs to be taken into account is, individuals are required to inculcate the traits of morality, ethics, diligence and resourcefulness. These are facilitating in carrying out all tasks and activities in a satisfactory manner and generating desired outcomes. Furthermore, one will be able to meet the expectations of other family members. Therefore, it can be stated, one will render an important contribution in promoting well-being and goodwill of their families, provided job duties are carried out in an efficacious manner. The main concepts that are taken into account in this research paper are, understanding meaning and significance of types and development processes of family, factors leading to development processes within families and advantages of encouraging development processes within families.